Smart Education for Slow and Fast Learners: An Adaptive Learning Approach - Upadhyay, Priya; Lashkari, Shruti; Mishra, Raj; Rathi, Nisha; Pawar, Rishikesh; Gadwal, Ashwinee (Recent Research Reviews Journal, 2025)
This study examines personalized learning within smart education to address the diverse needs of both fast and slow learners. Traditional teaching methods frequently neglect individual learning styles, resulting in disengagement and unequal academic performance. In this study, we provide customized learning materials and support to participants. Following a preliminary quiz that categorizes learners into distinct groups, personalized YouTube video tutorials are made available. Continuous internal assessments monitor progress, ensuring that learners receive the necessary support. A comprehensive course test concludes the evaluation process. Our analysis reveals significant performance disparities between slow and fast learners, highlighting the effectiveness of personalized learning in smart education. Slow learners demonstrate improved comprehension and retention, while fast learners excel with more challenging content. This underscores the importance of tailoring educational approaches to meet diverse learner needs, thereby promoting equitable learning outcomes in smart education environments.
Keywords: Smart Education; Slow Learners; Fast Learners; Prerequisite Quiz; YouTube Tutorials; Personalized Education; Educational Assessment